PENGARUH PENDEKATAN PEMBELAJARAN SOCIOSCIENTIFIC ISSUES TERHADAP KEMAMPUAN BERPIKIR KREATIF PESERTA DIDIK - Widia Rahmawati; Jujun Ratnasari; Suhendar Suhendar (Jurnal Pelita Pendidikan, 2018)
The purpose of this study is to examine the effect of Socioscientific Issues learning approach to improving students' creative thinking ability. Learning with the Socioscintific Issues approach needs to be trained because it not only develops creative thinking skills, but also other abilities can be developed such as critical thinking skills, decision-making and arguing ability. The research method that will be used is quasi experiment with Design Nonequivalent Control Group. This research was conducted at State Junior High School 6 Sukabumi with research population that is class VII (Seven). The sampling technique used is Purposing Sampling. Indicators of creative thinking that is sensitivity, thinking smoothly, thinking flexible, original thinking and thinking detailing. The results showed that the average value of N-gain of the experimental class was 0.56 higher than the control class of 0.44. The results of the z test show that the data produced in accordance with the criteria is zhitung = 3.177> ztabel = 1.998 with a trust level of 0.05 (5%), meaning H0 is rejected and H1 accepted, it means that the Socioscientific Issues learning approach influences the creative thinking ability of learners water pollution material. The response of learners to the learning approach Socioscientific Issue gave a positive response on the approach of learning approaches Socioscientific Issues.Keywords: Creative Thinking, Socioscientific Issues.